FORMALISTIC AND NARRATIVE IN PROJECTION MAPPING PAINTING: HABITAT - Achin, Imelda Ann; Bromeo, Addley Bianus (PEOPLE: International Journal of Social Sciences, 2015)
The projection mapping painting work entitled ‘Habitat’ is a creative production through the MATRIX project which emphasizes on the global warming issues towards the Borneo butterfly species in Sabah. In par with the advancement of technology in the producing of creative artworks, ‘Habitat’ applies the combination of technology into paintings to create an innovation in the acceptance of creative painting work. This article is a review of the formalistic aspect principles and the narrative projection mapping painting which emphasizes on cinematography and interpretation of story in the ‘Habitat’. The narrative chain is interpreted in the space and time according to the relevance of the materials experimented. In the context of using new digital media, artists need more research about a material to be featured in delivering a more effective narration.